HISTORICALLY WHITE UNIVERSITIES AND THE WHITE GAZE: CRITICAL REFLECTIONS ON THE DECOLONISATION OF THE LLB CURRICULUM1 (The Pretoria Student Law Review, 2021)
The (most recent) call for curriculum decolonisation came at the height of student protests such as #feesmustfall and #afrikaansmustfall. In the University of Pretoria’s Curriculum Transformation Framework document, the University identified four drivers of curriculum transformation, namely, responsiveness to social context; epistemological diversity; renewal of pedagogy and classroom practices; and an institutional culture of openness and critical reflection. The content of these drivers mirror what is needed to engage in decolonisation of curricula. In the spirit of these protests that led to the conceptualisation of decolonised higher education, the authors of this article critically reflect on the institutional landscape of historically white universities. The authors employ the term ‘white gaze’ to highlight how historically white universities respond to calls for decolonisation, often substituting this call with transformation. The purpose of this article is to re-contextualise the need for decolonisation at historically white universities.
Keywords: curriculum decolonisation; historically white universities; University of Pretoria’s Curriculum Transformation Framework